Validation of a French Version of the Career Decision-Making Difficulties Questionnaire: Relationships With Self-Esteem and Self-Efficacy. (August 2022) - Rossier, Jérôme; Rochat, Shékina; Sovet, Laurent; Bernaud, Jean-Luc
The aim of this study was to validate the French version of the Career Decision-Making Difficulties Questionnaire (CDDQ) and to assess its measurement invariance across gender, age groups, countries, and student versus career counseling samples. We also examined the sensitivity of this instrument to discriminate a career counseling population from a general student sample. Third, we studied the relationship between career decision-making difficulties, career decision-making self-efficacy, and self-esteem in a sample of 1, 748 French and French-speaking Swiss participants. A confirmatory factor analysis confirmed the overall hierarchical structure of the CDDQ. Multigroup analysis indicated that the level of invariance across groups almost always reached configural, metric, and scalar invariance. Differences between countries were very small, whereas differences between the general population and career counseling subsamples were much larger. Both self-esteem and self-efficacy significantly predicted career decision-making difficulties. Moreover, as expected, self-efficacy partially mediated the relationship between self-esteem and career decision-making difficulties.